THE INFLUENCE OF WEIGHTLIFTING ON THE PELVIC FLOOR MUSCULATURE STRENGHT IN WOMEN (Fiep Bulletin - online, 2015)
The aim of the present study is to verify the degree of contraction of the pelvic floor musculature with women aged between 20 to 30 years old, who have already practiced weightlifting for at least one year and to compare the subjective evaluation (functional) with the objective evaluation (perineometer). Ten women were evaluated by perineometry, and by functional evaluation by writing down the maximum amount of contraction. The parametric and paired t-test was used to compare the same group of women among the functional evaluation and the perineometer test, and also the Pearson correlation test, analyzing the correlation between the functional test and the perineometer test with height, weight, age and the practice of perineal exercises. There was statically difference between the two evaluations, obtained by the rating of p which was equal to p=0.0011, the difference presented statistically was significant (p
Keywords: Pelvic Floor; force; body lifting.